Determinants of employee turnover intention: Understanding the roles of organizational justice, supervisory justice, authoritarian organizational culture and organization-employee relationship quality. (7th August 2017) - Kim, Soojin; Tam, Lisa; Kim, Jeong-Nam; Rhee, Yunna
Abstract : Purpose: The purpose of this paper is to identify associations amongst organizational justice, supervisory justice, authoritarian culture, organization-employee relationship quality and employee turnover intention. Design/methodology/approach: An online survey ( n =300) was conducted in South Korea. Findings: Organizational justice and supervisory justice are positively associated with organization-employee relationship quality, while authoritarian organizational culture is negatively associated with it. In addition, there is a positive association between authoritarian organizational culture and turnover intention. Organizational justice and organization-employee relationship quality are negatively associated with turnover intention. Originality/value: This study contributes to the lack of research on organization-employee relationship quality as a predictor of employee turnover intention and a mediator between authoritarian organizational culture and turnover intention.